Implementasi Pijat Perut sebagai Terapi Komplementer : Pelatihan bagi Ibu Balita dalam Menangani Gas dan Kolik - Sumarni Sumarni; Kusumastuti Kusumastuti; Siti Mutoharoh; Dina Saskia Budiarti; Enjel Laksana P; Faizatun Hidayah; Jennie Sava Adela; Novi Wahyuni; Khusnul Khotimah (Lembaga Pengembangan Kinerja Dosen, 2025)
Bloating in infants can also accompany other digestive disorders, such as vomiting, diarrhea, abdominal pain, and constipation. Babies with gas often vomit easily. Babies with diarrhea will have low potassium levels, resulting in bloating. One benefit of infant massage is addressing complaints of bloating and colic in infants. Tummy massage is a gentle abdominal massage designed to encourage trapped air to move. The goal is to move gas and other materials from the intestines to the large intestine. The method used was preparation through coordination with midwives and cadres in Selokerto Village, Sempor District, Kebumen Regency. The activity was implemented through lectures and tummy massage simulations. While evaluation and follow-up plans for the activity were carried out by evaluating the knowledge of mothers of toddlers and can be implemented independently using leaflets distributed to mothers of toddlers. The number of respondents in this activity was 10 mothers of toddlers. The activity went smoothly, all mothers enthusiastically participated in the activity. Respondents were aged between 20-34 years. The level of knowledge of respondents before the activity was that most had sufficient knowledge about bloating/colic in toddlers and tummy massage. Meanwhile, after the knowledge activity, most responded well. Conclusion: The community service activity was effective in increasing respondents' knowledge about gas/colic in toddlers and tummy massage.